The Role of Artificial Intelligence (AI) in Productivity & Economic Growth in Nordic Welfare States - Butt, Junaid (Acta Universitatis Danubius. Œconomica, 2024)
The Nordic welfare states have long been admired for their robust social welfare systems and high standards of living. However, as these economies face challenges posed by demographic shifts and global economic competition, the role of artificial intelligence (AI) in driving productivity and economic growth becomes increasingly pertinent. This research explores the multifaceted relationship between AI, productivity, and economic growth in the context of Nordic welfare states. Drawing upon existing literature and empirical evidence, this study explores how AI can enhance worker capabilities by automating routine tasks, increase productivity across various sectors including manufacturing by optimizing resource allocation, public administration and driving innovation. Additionally, it investigates the mechanisms through which AI adoption influences economic growth, considering factors such as innovation, efficiency gains, and the creation of new industries and employment opportunities. Moreover, the study delves into the unique characteristics of Nordic welfare states, such as strong social safety nets and emphasis on human capital development, and assesses how these factors interact with AI-driven productivity and economic growth. Furthermore, the study examines policy implications, including the need for adaptive regulatory frameworks, investment in AI infrastructure and research, and strategies for up-skilling the workforce to ensure inclusive growth and social cohesion. By offering insights into the role of AI in shaping productivity and economic growth within Nordic welfare states, this research contributes to a deeper understanding of the opportunities and challenges presented by AI adoption in the context of advanced social welfare models. The study emphasizes the significance of social safety nets in Nordic welfare states and the need for re-skilling and up-skilling to prevent job displacement. It also explores the potential of AI adoption in these states, aiming to inform policymakers and stakeholders on strategies to maximize the benefits of AI while maintaining social cohesion.